Feelings: shy. ([s.l.]: Pegasus)
Do you feel shy in class? Do you feel shy when you meet new people? Here's a lovely, read-aloud book that explores situations that may make little ones feel shy. The book is a gentle and perfect way to help toddles understand their feelings of shyness.